2012
DOI: 10.1017/s1074070800000237
|View full text |Cite
|
Sign up to set email alerts
|

The Motivation for Organic Grain Farming in the United States: Profits, Lifestyle, or the Environment?

Abstract: The objective of this research is to identify and quantify the motivations for organic grain farming in the United States. Survey data of US organic grain producers were used in regression models to find the statistical determinants of three motivations for organic grain production, including profit maximization, environmental stewardship, and an organic lifestyle. Results provide evidence that many organic grain producers had more than a single motivation and that younger farmers are more likely to be motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
(54 reference statements)
5
28
0
Order By: Relevance
“…However, the West German study also found that environmental concerns alone are not enough to predict organic agriculture adoption, and a key factor was if farmers found the decision to go organic 'economically very attractive' (p. 464). A related finding has been reported by Peterson et al (2012) and also by Lapple and Van Rensburg (2011) and others (Läpple, 2010;Kaufmann et al, 2011), who found that environmental concerns positively correlate with the organic agriculture adoption decision.…”
Section: Adoption Of Transformative Agriculture Technologiessupporting
confidence: 77%
See 1 more Smart Citation
“…However, the West German study also found that environmental concerns alone are not enough to predict organic agriculture adoption, and a key factor was if farmers found the decision to go organic 'economically very attractive' (p. 464). A related finding has been reported by Peterson et al (2012) and also by Lapple and Van Rensburg (2011) and others (Läpple, 2010;Kaufmann et al, 2011), who found that environmental concerns positively correlate with the organic agriculture adoption decision.…”
Section: Adoption Of Transformative Agriculture Technologiessupporting
confidence: 77%
“…While organic producers may be willing to accept greater risk, they also are motivated by the potential for higher profit margins associated with organic products (McCann et al, 1997). In a corresponding finding, Peterson et al (2012) found that the motivations of organic grain farmers in the USA extend beyond organics as a way of life to include profit maximization.…”
Section: Adoption Of Transformative Agriculture Technologiesmentioning
confidence: 99%
“…Other studies that surveyed farmers have experienced low response rates (e.g., 21.9 percent by Peterson et al, (2012) and 20 percent by Ryan, Erickson, & De Young, (2003)). In a study investigating the notoriously low survey response rates of farmers, Pennings, Irwin, and Good (2002) found that providing incentives, creating shorter surveys, and choosing the right time of year can help to increase response rates.…”
Section: Study Participantsmentioning
confidence: 98%
“…Peterson, Barkley, Chacon-Casante, Kastens, Marchant, and Bosch (2012) found that organic grain and soybean farmers in the U.S. were motivated to produce organic products by multiple factors, including economic and environmental ones, and that younger farmers were more likely to be motivated by environmental and lifestyle factors than older farmers. Ryan, Erickson & De Young (2003) surveyed Michigan farmers to learn about their motivations for adopting conservation practices and found that rather than economic reasons, farmers were intrinsically motivated to adopt conservation practices because of their attachment to the land.…”
Section: Motivation Among Local Food System Playersmentioning
confidence: 99%
“…Contract marketing is a potential alternative in the agriculture system to establish a market linkage between smallholder farmers and the retailers (Man and Nawi, 2010;Kirsten and Sartorius, 2002). Motivation such as price premium for certified organic products, sales channel access capabilities, economic sustainability and valorizing the local development are among the main concerns for farmers' participation in organic farming (Peterson et al, 2012). Contract marketing is an incentive and insurance for small scale farmers involved in environmental improvement activities such as organic practices.…”
Section: Introductionmentioning
confidence: 99%